A = 5+52+53+.....+52011
A5 = (5+52+53+.....+52011).5
A5 = 52+53+54+.....+52012
A5 - A = (52+53+54+.....+52012)-(5+52+53+.....+52011)
A4 = 52+53+54+.....+52012 - 5-52-53-.....-52011
A4 = 52012 -5
A = (52012 -5) :4
Mà 4A + 5 = 5N => 4 (52012 -5) :4 + 5 = 5N => 52012 -5 + 5 = 5N => 52012 = 5N => N = 52011
\(A=5+5^2+5^3+...+5^{2011}\)
\(5A=\left(5+5^2+5^3+...+5^{2011}\right)\times5\)
\(5A=5^2+5^3+5^4+...+5^{2012}\)
\(5A-A=\left(5^2+5^3+5^4+...+5^{2012}\right)-\left(5+5^2+5^3+....+5^{2011}\right)\)
\(4A=\left(5^2+5^3+5^4+....+5^{2011}\right)-\left(5^2+5^3+5^4+....+5^{2011}\right)+\left(5^{2012}-5\right)\)
\(4A=0+\left(5^{2012}-5\right)=5^{2012}-5\)
\(\Rightarrow4A+5=5^{2012}\)hay \(5^n=5^{2012}\)
\(\Rightarrow n=2012\)